Anti-IL6 treatment of serious COVID-19 disease: A monocentric retrospective experience. Issue 1 (8th January 2021) - Castelnovo, Laura; Tamburello, Antonio; Lurati, Alfredo; Zaccara, Eleonora; Marrazza, Maria Grazia; Olivetti, Micol; Mumoli, Nicola; Mastroiacovo, Daniela; Colombo, Daniele; Ricchiuti, Elisabetta; Vigano', Paolo; Paola, Faggioli; et al.
Abstract : Abstract: COVID-19 is causing a high influx of patients suffering from serious respiratory complications leading the necessity to find effective therapies. These patients seem to present with cytokine perturbation and high levels of IL6. Tocilizumab and sarilumab could be effective in this condition. We retrospectively collected data about 112 consecutive hospitalized in a single center. Fifty (IL6 group) treated with tocilizumab (8 mg/kg intravenously [IV], 2 infusions 12 hours apart) or sarilumab 400 mg IV once and 62 treated with the standard of care but not anti-cytokine drugs (CONTROL group). To determine whether anti-IL6 drugs are effective in improving prognosis and reducing hospitalization times and mortality in COVID-19 pneumonia. To date 84% (42/50) of IL6 group patients have already been discharged and only 2/50 are still recovered and intubated in intensive care. Six/fifty patients (12%) died: 5/6 due to severe respiratory failure within a framework of severe acute respiratory distress syndrome (ARDS), 1 suffered an acute myocardial infarction, and 1 died of massive pulmonary thromboembolism. There were no adverse treatment events or infectious complications. Compared to the CONTROL group they showed a lower mortality rate (12% versus 43%), for the same number of complications and days of hospitalization. Anti-IL6 drugs seem to be effective in the treatment of medium to severe forms of COVID-19 pneumonia reducing the risk of mortality due to multi-organ failure, acting at the systemic level and reducing inflammation levels and therefore microvascular complications. However, it is essential to identify the best time for treatment, which, if delayed, is rendered useless as well as counterproductive. Further studies and ongoing clinical trials will help us to better define patients eligible as candidates for more aggressive intervention.